The role of the judiciary in the public decision making process - Giuseppe Albanese; Marco M. Sorge (Max Planck Institute for Research on Collective Goods, 2010)
In this paper we investigate the role of judicial control of lobbying activities in an endogenous policy framework, focusing on two dimensions of quality of the judiciary, namely efficiency and integrity. We present a multi-layer lobbying model where a self-interested group is allowed to inuence a public decision maker - and possibly the judicial authority itself, which performs an anti-corruption task - with the payment of illegal contributions, and provide general conditions for the existence of a zero-contribution equilibrium. Furthermore, we study how sensitive the main findings are to different institutional arrangements as to judicial independence.
Keywords: D72; D73; D78; H11; H49; H77; 330; Illegal lobbying; Endogenous policy making; Judicial control; Justiz; Rechtsdurchsetzung; Interessenpolitik; Korruption; Public Choice; Theorie